Acceleration of target production in co‐culture by enhancing intermediate consumption through adaptive laboratory evolution. Issue 3 (28th December 2021) - Kawai, Ryutaro; Toya, Yoshihiro; Miyoshi, Kenta; Murakami, Manami; Niide, Teppei; Horinouchi, Takaaki; Maeda, Tomoya; Shibai, Atsushi; Furusawa, Chikara; Shimizu, Hiroshi
Abstract: Co‐culture is a promising way to alleviate metabolic burden by dividing the metabolic pathways into several modules and sharing the conversion processes with multiple strains. Since an intermediate is passed from the donor to the recipient via the extracellular environment, it is inevitably diluted. Therefore, enhancing the intermediate consumption rate is important for increasing target productivity. In the present study, we demonstrated the enhancement of mevalonate consumption in Escherichia coli by adaptive laboratory evolution and applied the evolved strain to isoprenol production in an E. coli (upstream: glucose to mevalonate)– E. coli (downstream: mevalonate to isoprenol) co‐culture. An engineered mevalonate auxotroph strain was repeatedly sub‐cultured in a synthetic medium supplemented with mevalonate, where the mevalonate concentration was decreased stepwise from 100 to 20 µM. In five parallel evolution experiments, all growth rates gradually increased, resulting in five evolved strains. Whole‐genome re‐sequencing and reverse engineering identified three mutations involved in enhancing mevalonate consumption. After introducing nudF gene for producing isoprenol, the isoprenol‐producing parental and evolved strains were respectively co‐cultured with a mevalonate‐producing strain. At an inoculation ratio of 1:3 (upstream:downstream), isoprenol production using the evolved strain was 3.3 times higher than that using the parental strain. Abstract : One of the bottlenecks for co‐culture‐based bio‐production is an intermediate metabolite uptake ability of the downstream strain. Here, we demonstrate an enhancement of mevalonate uptake rate of E. coli by adaptive laboratory evolution for enhancing isoprenol production in E. coli‐E.coli co‐culture.